Riba Dalam Al-Quran Dan Strategi Menghadapinya - Ahmad Naufal (Al Maal: Journal of Islamic Economics and Banking, 2019)
The systemic practice of usury has caused the monetary sector to separate from the real sector, causing a prolonged economic downturn. This has actually been warned in the Qur'an. For this reason, this study aims to explore the "warning" about usury in the Qur'an, including finding  solutions. With the method of interpretation of maudhu'i's conclusions, it was concluded that the prohibition of usury because of usury contained dangers and impacts both micro and macro. The gradual prohibition of usury gives an understanding that in order to deal with the usury system a planned stage and strategy is needed. And the main strategy to deal with the usury system is to promote charity and alms.